La representación como acción articuladora entre forma y proyecto: un taller de morfología como caso de estudio - Sanjurjo, Moira (2018)
The tradition of teaching representation in the faculties of architecture in Argentina, established a division between the universe of artistic drawing and technical-geometric drawing, according to the disciplinary fields‘fragmentation, typical of the thought of the time. The cultural changes that took place in the first half of S XX, both in art and in the scientific field, suggested ruptures in higher education models that were concretized in new plans of studies, where the representational universe was included in the Morphology Area. The present work proposes to make a contribution to the representation teaching from a view situated in a contemporary thinking that assume the form as a cultural product, the project as a mode of operation and to the representation as a cognitive action.